Género e Música Electrónica de Dança : Experiências, percursos e 'retratos' de mulheres clubbers - Guerra, Paula (2009)
This report is supported by two central axes of analysis: first, understanding female clubbers' experiences and identity constructions of gender in clubbing in Porto (Portugal) [focusing the analysis on techno, drum'n'bass and trance]; second, how to connect club (sub)cultures with wider social structures, while analysing their specific inner structures.